Proceedings of the Fifth International Workshop New Worlds in Astroparticle Physics : Faro, Portugal, 8-10 January 2005 - Mourão, Ana M. (World Scientific, 2006)
In international workshops on "New Worlds in Astroparticle Physics" held biannually, astronomers, astrophysicists and particle physicists discuss recent developments in the exciting and rapidly developing field of Astroparticle Physics. Similar to previous workshops, this 5th international workshop introduced experimental, observational and theoretical subjects through review lectures. This was followed by shorter contributions on the recent developments in Astroparticle Physics. This workshop covered an array of subjects like cosmic rays, gravitational waves, space radiation, neutrino physic.